Hubungan Keragaman Pangan dengan Kejadian Stunting - Wulan Margiana; Evicenna N Riani; Ima Syamrotul M (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2021)
Stunting is a nutritional problem in the world, there are 165 million children under five in the world who are stunted. Eighty percent of children under five with stunting are spread across 14 countries in the world and Indonesia is in the fifth rank of the countries with the largest number of stunting. Stunting data in Indonesia shows that the national prevalence of stunting has increased from 35.6% (2010) to 37.2% (2013). This condition illustrates that around 8.9 million Indonesian children experience slow growth or one in three children is stunted. Based on a stunting survey study conducted in 2018, Banyumas Regency is included in the top 100 districts / cities with the highest stunting rate in Indonesia. Banyumas is one of the areas selected to be the priority in handling children under five stunting cases in Central Java along with nine other districts or cities. Rempoah Baturaden Village is one of the priority targets in an effort to reduce stunting in Banyumas district. The purpose of this study was to determine the relationship between food diversity and the incidence of stunting in the village of Rempoah Baturaden, Banyumas Regency. The research method used was analytic observational research, with a cross sectional design. The results show that there is a relationship between food diversity and the incidence of stunting in Rempoah Baturaden Village, Banyumas Regency.